Three new species of penicillate millipedes from the Con Dao Islands of southeast Vietnam (Diplopoda, Lophoproctidae and Polyxenidae) - Huynh, Cuong; Veenstra, Anneke A (Zootaxa, 2020)
We describe three new penicillate millipede species from Con Dao Archipelago in southeastern Vietnam: Alloproctoides consonensis n. sp. (Lophoproctidae), Monographis condorensis n. sp. (Polyxenidae), and Unixenis moniqueae n. sp. (Polyxenidae). Comparative morphological and genetic studies based on 18S and COI genes indicate that all three species differ from previously described species.